The Effect of Children’s Phubbing on Parents’ Psychological Wellbeing: A Moderated Mediation Analysis - Yeslam Al-Saggaf; Rachel Hogg (Human Behavior and Emerging Technologies)
Attending to the phone while interacting face-to-face with another person, a behaviour known as phubbing, can be detrimental to the phubbed person’s psychological wellbeing. Recent research revealed that phubbing friends and partners indirectly affected the phubbed individual’s wellbeing. The aim of this study was to investigate the effect of children’s phubbing on parents’ psychological wellbeing; not the effect of parents’ phubbing on children’s psychological wellbeing, which has been the focus of most of current research. Two hundred and sixty six (266) parents of smartphone users participated in a web survey. The questionnaire measured parents’ experience of being phubbed by their children, psychological wellbeing, relationship satisfaction, loneliness, and self-esteem. The analysis showed a significant indirect effect of children’s phubbing on parents’ psychological wellbeing through the mediating roles of relationship satisfaction and loneliness. Children’s phubbing increased parents’ feelings of loneliness, and this rise in levels of loneliness worsened parents’ psychological wellbeing. Similarly, children’s phubbing decreased parents’ relationship satisfaction with their children, and this decrease in feelings of relationship satisfaction worsened parents’ psychological wellbeing. Additionally, children’s phubbing affected parents’ psychological wellbeing through the mediating roles of relationship satisfaction and loneliness in sequence (chain effect). As children’s phubbing increased parents’ feelings of loneliness, parents’ relationship satisfaction with their children dropped. The lowering of feelings of relationship satisfaction worsened parents’ psychological wellbeing. A moderated mediation analysis revealed that children’s phubbing decreased parents’ relationship satisfaction with their children, especially for parents who are low on self-esteem. This study is one of the first that offers insights into how children’s phubbing and parents’ psychological wellbeing are related.